(untitled) (Scientia Agricola, 2013)
Pitaya (Hylocereus undatus) is an exotic non-climacteric fruit that reaches its best eating quality when harvested ripe, decreasing thereafter during storage. Our objectives were to determine the best combination of storage temperature and use of perforated plastic bags to maintain the postharvest quality of the fruit. Fruits were stored at 5, 7, or 10 ºC with and without a perforated plastic bag for 20 days, followed by five days at 20 ºC without the bag for shelf-life determination. Storage at 5 ºC, followed by 7 ºC maintained better visual appearance of the pitaya fruit after 20 days, by reducing decay incidence and severity, and maintaining greener bracts compared with fruit stored at 10 ºC. Pitaya fruit stored at 5 ºC without a perforated plastic bag showed no decay after storage and shelf-life. In general, higher temperatures and the use of a perforated plastic bag increased decay incidence, as well as decay severity after storage and shelf-life conditions. At all temperatures, fruit stored in a perforated plastic bag had lower weight loss during storage. After shelf-life, weight loss was highest in fruit stored at higher temperatures. Storage of fruits at 5 ºC resulted in minor chilling injury symptoms in the outer flesh tissue, close to the peel. Storage at 5 ºC without a perforated plastic bag was the best condition to maintain the postharvest quality of the pitaya fruit.